Yield estimate (230 kt) for a Mueller-Murphy model of the 3 september 2017, North Korean nuclear test (mbNEIC = 6.3) from teleseismic broadband P waves assuming extensive near-source damage - Chaves, Esteban (2018)
The 3 September 2017 underground nuclear test (mbNEIC= 6.3) is the largest of six announced North Korean explosions. The event generated many P wave seismograms at global broadband seismic stations with good signal-to-noise ratio for periods less than ~5 s. Instrument deconvolution provides 435 stable broadband P wave ground displacement records in the period range 0.1 to 5.0 s. These are stacked in 26 azimuth/distance windows to average path and receiver effects. Waveform stacks and average amplitude of 4-Hz ground displacements are modeled assuming a Mueller-Murphy explosion source modelfor a granite source medium. Nonelastic pP delays consistent with burial depths in the mountainous source topography are considered, and explosion yield and an average constant-Q attenuation operator areestimated by fitting the waveforms. For a source depth of 750 m in heavily damaged environment, the estimated yield = 230 ± 50 kt andt*= 0.78 ± 0.03 s.